Environmental variability patterns in the Peruvian waters - Flores, Roberto (2013)
Environmental scenarios and variability patterns observed in the Peruvian waters are described based on the analysis of information obtained by the Instituto del Mar del Peru between 1960 and 2011. This information includes data from oceanographic, stock assessment and bio-oceanographic scientific research surveys, published information was also used to complete this study. Sea temperature, salinity and oxygen content data was interpolated to obtain monthly averages and build temporal and spatial series. Surface Cold Coastal Waters (ACF) and Subtropical Surface Water (SSW) create environmental conditions that are different from those in the subsurface, where the intrusion of equatorial waters dominates through the Peru-Chile Subsurface Current (CSPC). In the north, during the summer and fall, there is predominance in the surface layer of waters from the equatorial system. In the central zone the equatorial waters interact with ACF from coastal upwelling. The south is more strongly influenced by the coastal upwelling and the ASS, which is an indicator of increased activity in the Current System of Peru (SCP).